Mathematical models of chlorine demand in surface waters: A systematic review - Barzola Choque, Carmen Juana (2024)
The mathematical model of water quality is a simplified representation of reality and constitutes a support tool to know a priori the changes in chemical or biological quality that occur throughout the river basin and useful for decision-making. decisions of the authorities in the management of water resources and the administration of water service providers. The objective of the article is a systematic review of the models that have been developed for the prediction of chlorine demand in water. From the review, seven models developed for the estimation of chlorine demand have been identified, which shows that it is a line of research to be explored. These models were built based on experimentation in the laboratory, in the Plant and data of previous studies, accompanied by tests of the estimate of the predictive capacity of the model, with the exception of some cases. This review is a contribution to the knowledge of the demand for chlorine, being of interest to the companies that provide services and actors in the management of water resources to have predictive tools on natural and anthropic phenomena that occur, interact and generate pollution in a hydrographic basin.